SMaRtTrie: Reducing Checkpoint’s Impact in SMR Systems with a CTrie Data Structure - Pintor, Erick; Dotti, Fernando Luís (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2021: Anais do XXXIX Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2021)
State Machine Replication (SMR) is a well-established approach for the development of fault tolerant systems through replication. Durable SMR systems rely on command logging and checkpoints for fast recovery upon failures. However, checkpoints are known to impact service's throughput as traditional SMR architectures stop serving requests in order to ensure checkpoint consistency. In this paper, we present SMaRtTrie: a simple in-memory key-value storage built on a concurrent trie data structure that supports the creation of consistent checkpoints in parallel with command execution. Experimental evaluation shows that SMaRtTrie can reach the same throughput as other commonly used solution while sustaining 78% throughput during checkpoints.